DEVELOPMENT OF MANAGEMENT SCIENCES, INFORMATION SCIENCES, COMPUTER SCIENCES - Akramov Izzat Ikromovich (Scholar Express Journals, 2024)
A description of the characteristic features of this area of knowledge, which is the scientific basis for the development of the future generation of information technologies, is given. Development of management sciences, information sciences, computer sciences were also analyzed. In addition, the basics of development of informatics and management control were studied.
Keywords: information science; computer science; informatics as computer and information science